IDENTIFIKASI GULMA PADA DUA TIPE PERKERASAN TAMAN (KONBLOK DAN GRASBLOK) - Siti Nurisjah; A. Pieter Lontoh (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 1995)
Weed constitute one the main problems encountered in urban parks, including those growing on paved park grounds, because in addition to impairing the beauty of the parks they also reduced their function and durability. By weed inventory on park grounds management actions can be planned and conducted Field observation were carried out for two months at the "Monumen Nasional" grounds in Jakarta. Two widely used types of pavement were selected, i.e. conblock and grassblock. The Dominance Value Summed Dominance Ratio were calculated using Tjitro Soedirdjo. Three groups of wide grew in this area, i.e. broad leaves weeds, grasses, and sedges. The species growing on both types of pavement and in both ecological condition are Cyperus rotundus, Eleusine indica, and Euphorbia thymyfolia. Eleven species were identified on shaded and on open conblock respectively. Of these species, nine species grew on both condition, but at varying level of dominance. These are Euphorbia thymifolia, Eleusine indica, Cyperus rotundus, Hedyotis corymbosa, Portulaca oleraceae, Axonopus compressus, Ricahardia brasiliensis, Bacopa procumbens, and Synedrella nodiflora. Eight species were found on shaded grassblock and nine species on open grassblock. Species were found in both condition, i.e. Cyperus rotundus, Eleusine indica, Euphorbia thymyfolia, Chrysopogon aciculatus, and Borreria repens.